2019
DOI: 10.3319/tao.2018.09.28.01
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structure of the Milun Fault from surface ruptures of the 2018 Hualien Earthquake

Abstract: A deadly M w 6.4 earthquake occurred in the Hualien area of eastern Taiwan on 6 February 2018. It caused severe damage to infrastructure and creating surface ruptures in several areas mostly near the Milun Fault in Hualien City. In this study, we investigated the distribution of co-seismic surface ruptures by measuring the orientations of the ruptures, classifying the fracture patterns, and measuring the fracture geometries to calculate the principal displacement zone (PDZ) and the regional stress directions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The measured data were generally self-consistent with nearby measurements. Field measurements (Hsu et al , 2019Huang et al 2019;Lin et al 2019) showed that the fault has left lateral motion of around 70 cm near the Chihsingtan village, which was comparable to our result in the same area. The campaign and continuous GPS data were also comparable to our current results as seen in both Figs.…”
Section: Disscussion and Conclusionsupporting
confidence: 90%
See 2 more Smart Citations
“…The measured data were generally self-consistent with nearby measurements. Field measurements (Hsu et al , 2019Huang et al 2019;Lin et al 2019) showed that the fault has left lateral motion of around 70 cm near the Chihsingtan village, which was comparable to our result in the same area. The campaign and continuous GPS data were also comparable to our current results as seen in both Figs.…”
Section: Disscussion and Conclusionsupporting
confidence: 90%
“…As inferred from the distribution of the aftershock, which ranged from the offshore Milun Fault to the Great Hualien area on land, the seismogenic fault should be a strike-slip fault with a westward dip in a northeast-southwest direction. The shock induced the activities on the Milun Fault and the Lingding Fault and caused a large-scale of surface ruptures along the fault line (Hsu et al , 2019Huang et al 2019;Lin et al 2019) -mainly concentrated at the north of Hualien County (Fig. 2 The Milun Fault is a left-lateral fault with a reverse component striking in a direction of north-south and extending from the southwest of the Chihsingtan beach to Hualien City along the west edge of the Milun Terrace.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that surface ruptures follow the traces of the Milun fault and northern Linding fault. The mapped surface ruptures are typically appeared in en échelon arrays or distributed fractures rather than a through-going fault, which are comparable to the results of Hsu et al (2019) and Huang et al (2019). They considered that the appearances of the along-strike variations of the surface rupture for the 2018 Hualien earthquake are different from the surface rupture patterns documented for the 1951 Hualien-Taitung event.…”
mentioning
confidence: 64%
“…Independently Hsu et al (2019) conducted field surveys along the Milun fault and examined the coseismic ruptures of the 2018 Hualien event. In addition to the rupture geometry, they determined the principal displacement zone and Terr.…”
mentioning
confidence: 99%